2019
DOI: 10.1128/jvi.01714-18
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-Mediated Knockout of DNAJC14 Verifies This Chaperone as a Pivotal Host Factor for RNA Replication of Pestiviruses

Abstract: Pestiviruses like bovine viral diarrhea virus (BVDV) are a threat to livestock. For pestiviruses, cytopathogenic (cp) and noncytopathogenic (noncp) strains are distinguished in cell culture. The noncp biotype of BVDV is capable of establishing persistent infections, which is a major problem in disease control. The noncp biotype rests on temporal control of viral RNA replication, mediated by regulated cleavage of nonstructural protein 2-3 (NS2-3). This cleavage is catalyzed by the autoprotease in NS2, the activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 106 publications
2
24
0
Order By: Relevance
“…Alternatively, by selectively disrupting HIV proviral DNA integrated into the host genome, some groups have demonstrated that targeting HIV long terminal repeats (LTRs) or essential viral genes is an effective approach to profoundly suppress HIV production in vitro [57][58][59][60][61][62] and in vivo 63 . However, there are no dsDNA intermediates in the majority of RNA viruses, and host essential genes are the only choice for CRISPR/ Cas9 targeting, including for TGEV 64 , IAV 65 , CSFV 66 , FMDV 67 and BVDV 68 . A recent study described the application of CRISPR/Cas9 to pig zygotes, resulting in the generation of pigs with a deletion of exon 7, which encodes SRCR5 of the CD163 gene responsible for binding to GP4 to mediate viral entry.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, by selectively disrupting HIV proviral DNA integrated into the host genome, some groups have demonstrated that targeting HIV long terminal repeats (LTRs) or essential viral genes is an effective approach to profoundly suppress HIV production in vitro [57][58][59][60][61][62] and in vivo 63 . However, there are no dsDNA intermediates in the majority of RNA viruses, and host essential genes are the only choice for CRISPR/ Cas9 targeting, including for TGEV 64 , IAV 65 , CSFV 66 , FMDV 67 and BVDV 68 . A recent study described the application of CRISPR/Cas9 to pig zygotes, resulting in the generation of pigs with a deletion of exon 7, which encodes SRCR5 of the CD163 gene responsible for binding to GP4 to mediate viral entry.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that endogenous levels of DNAJC14 are vital for YFV replication [57]. A similar role of DNAJC14 has recently been observed in the RNA replication of the bovine viral diarrhea virus (BVDV) [59]. Therefore, DNAJC14 is a key host cell factor for flavivirus replication.…”
Section: Er Proteins Required For Flavivirus Replication and Assemmentioning
confidence: 75%
“…The geminivirus-silencing suppressor βC1 was recently shown to activate and be degraded by host autophagy to reduce viral virulence ( Ismayil et al, 2020 ). Cellular peptidylprolyl isomerases or protein chaperones regulate polyprotein cleavage kinetics and the persistence of human and animal viruses, such as the hepatitis C virus, yellow fever virus, and bovine viral diarrhea virus ( Kaul et al, 2009 ; Bozzacco et al, 2016 ; Isken et al, 2019 ). More recently, a functional link between polyprotein processing and host RNA metabolism was reported in alphaviruses.…”
Section: Discussionmentioning
confidence: 99%
“…Virus-encoded proteases are multifunctional hubs that coordinate virus replication and host–virus interactions to promote infectivity and virulence ( Martínez et al, 2016 ; Lei and Hilgenfeld, 2017 ; Rodamilans et al, 2018 ). The spatial-temporal regulation of protease activity and the processing of viral polyproteins can further determine viral persistence and disease lethality ( Lackner et al, 2004 ; Yost and Marcotrigiano, 2013 ; Isken et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%